Mediating role of psychological contract breach between workplace bullying, organizational commitment & employee turnover intentions - Muhammad Shaukat Malik; Shahzadi Sattar; Rana Muhammad Shahid Yaqub (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
A plethora of researches about the repercussions of workplace bullying has depicted the negative employee emotional reactions, particularly neglecting the rational understanding behind this phenomenon. The current research examines the effect of workplace bullying on organizational work related outcomes. Researchers integrated the social exchange theory, attribution theory and social learning theory so as to suggest and present a model where the inverse association between workplace bullying and organizational commitment is vindicated by psychological contract breach. Furthermore, the positive association between workplace bullying and employee turnover intentions is also explained by psychological contract breach. The research also highlights the employees' beliefs that when an organization declines to meet its commitments towards its employees the organization has to bear repercussions. In the current study, data was collected from 320 employees of field setting. Results clearly revealed that workplace bullying causes psychological contract breach and it serves as the mediator workplace bullying, employee turnover intentions and organizational commitment. Our results of mediation clearly reflect that effects of bullying deteriorate the organizational commitment as well.
Keywords: 330; workplace bullying; organizational commitment; employee turnover intentions; psychological contract breach